INTRODUCTION OF AGRICULTURAL CROP RESIDUES AS SUPPLEMENT FOR GOATS FATTENING AMONG ANIMAL REARERS IN GIPALMA MUBI-SOUTH, ADAMAWA STATE - Babale; Aliyu, A.; Dazala; Wazamda (International Journal of Research -GRANTHAALAYAH, 2018)
Fattening has been defined as intensive feeding of highly nutritious feed to and promotes fast growth and fat deposition to achieve desired carcass growth and quality. The main strategy is to fatten young, lean male goat to obtain either from the farmer’s own flock or more often, purchased on the open market over a period of two to three months, with each farmer fattening between one and five animals. The goats are usually tethered or kept in a small sheltered enclosure at the homestead, and often fed and watered individually. Basal feeds used for goat fattening, such as hay and millet straw are supplemented with cowpea haulms, maize bran, rice bran and coconut flour which is derived from the crop residues. Poor nutrition is a major constraint in fattening small ruminants in Nigeria, this is because farmers often give the animals whatever is available, leading to waste when feed availability is high, and underfeeding when it is low (feed availability). Fattening of small ruminants as a business is very common in Nigeria. Small ruminants are usually reproduced on the farms or houses and are sold around festivities. (Christmas and Sallah) or when cash is required. No special efforts, other than grazing the animals, are made by many smallholder farmers and pastoralists to ‘’fatten’’ them. A similar situation exists for fattening of large ruminants (bulls) as a business. Most farmers in Nigeria sell their bulls once they have been introduced to ‘’fatten’’ these animals commercially. Goats are able to subsist and make appreciable gains in long dry season with crop residue-based diets that compare favourably with conventional concentrate rations. Some of the crop residues and by-products available are potentially good feed resources which degrade readily in the rumen, some however, have shown poor degradability and hence, require some treatments before they can contribute to animal nutrition.